PROSES BERPIKIR KREATIF DALAM PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI TIPE KEPRIBADIAN DIMENSI MYER-BRIGGS SISWA KELAS VIII MTs NW SURALAGA LOMBOK TIMUR TAHUN PELAJARAN 2013/2014 - Aziz, Abdul; Kusmayadi, Tri Atmojo; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2014)
Abstract: This study aimed at describing the process of creative thinking of the eight grade students of MTs NW Suralaga East LombokÂ in the academic year of 2013/2014, who had personality type based on the Myer-Briggs personality dimensions, namely rational personality type (STR) and guardian personality type (STG) in the mathematics problems solving on Wallas steps, namely preparation, incubation, illumination, and verification. The approach used descriptive qualitative approach in a case study. The data collection technique was conducted by using task based interview. The result showed that the procces of creative thingking on: (1) the STR students, namely: (a) the preparation, the students read APS (assignment problem solving) silently, observed the instructions and information carefully, and mentioned the known and the asked things inÂ reading once APS; (b) incubation, the students tend to be silent for a moment, the students do a contemplation activities, planned the problem solving, and took a long time to bring up the idea; (c) illumination, the students started by identifying the contained information in the APS, wrote how to solve the problem and continued by explaining the procedure of problem solving, the students established the steps to resolve the problem and got the idea by developing the idea of the previous answers; (d) verification, the students expressed orally the re-examination procedure of the answer, wrote the re-examination procedure, explained the re-examination procedure and explained the procedure again orally. (2) The STG students, namely: (a) the preparation, the students read the APS silently, and in a loud voice, mentioned the current issues in the APS, wrote the problems on the answer sheet, mentioned the known and the asked things of APS after a given follow-up questions; (b) incubation, the students tend to be silent, the students do a contemplation activities and arranged the plan of problem-solving when they were calm; (c) illumination, the students identified the information on APS and determined the attributes that were used to solve the problem, established the steps to resolve the problem, described the problem solving procedures, solved the problems by developing the idea from the previous idea; (d) verification, the students revealed and explained the re-examine procedure of the answer orally, wrote the re-examination procedure of the answer, observed and re-checked the problem solving that had been done.Keywords: Creative Thinking, Problem Solving, and Personality Type